MUTANAQISHAH MUSYARAKAH (MMQ) PADA PERBANKAN SYARIAH DALAM PERSPEKTIF MAQASHID SYARIAH - Kamaruddin; Misno (JURNAL ALAMIAH, 2021)
This study aims to analyze the implementation of musyarakah mutanaqishah contracts (MMq) in the development of sharia development in Indonesia from the perspective of Maqashid Syariah. The research method used is a mixed method, which combines library research that emphasizes qualitative philosophical analysis and field research. Primary data was obtained through observation, interviews and document review on four Islamic banks in Makassar City. Next, the data was analyzed using the philosophical qualitative method and the sharia maqashid approach. The result of this study is that the implementation of musyarakah mutanaqishah (MMq) in Islamic banking in Makassar City is in the form of financing for property (houses), vehicles and other objects. Akad musyarakah mutanaqishah in the Maqashid Shariah Perspective can be seen from the protection of religion, life, intellect, lineage and property.